Packet types abstract specification of network protocol messages. - McCann, Peter J. (Computer communication review.)
In writing networking code, one is often faced with the task of interpreting a raw buffer according to a standardized packet format. This is needed, for example, when monitoring network traffic for specific kinds of packets, or when unmarshaling an incoming packet for protocol processing. In such cases, a programmer typically writes C code that understands the grammar of a packet and that also performs any necessary byte-order and alignment adjustments. Because of the complexity of certain protocol formats, and because of the low-level of programming involved, writing such code is usually a cumbersome and error-prone process. Furthermore, code written in this style loses the domain-specific information, viz. the packet format, in its details, making it difficult to maintain.